2011
DOI: 10.1007/s13224-011-0076-x
|View full text |Cite
|
Sign up to set email alerts
|

Hysterectomy…..Which Route?

Abstract: Objective We designed this study to focus on women with mobile uteri benign no larger than 14 weeks, who would ordinarily be considered candidates for vaginal hysterectomy and compare the outcomes when abdominal routes were chosen. We also compared the intra and post operative complications, requirement for blood transfusion, length of hospital stay, between abdominal and vaginal route of hysterectomy. Method In a simple randomized prospective comparative study 200 consecutive patients requiring hysterectomy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 10 publications
3
7
0
Order By: Relevance
“…However, in our study, we did not have any major intraoperative complications. Studies by Chakraborty et al and Shanthini et al encountered bladder and ureteric injuries in the abdominal hysterectomy group [ 5 , 8 ]. This difference may be attributed to the skill of the operating surgeon and the complexity of the case.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, we did not have any major intraoperative complications. Studies by Chakraborty et al and Shanthini et al encountered bladder and ureteric injuries in the abdominal hysterectomy group [ 5 , 8 ]. This difference may be attributed to the skill of the operating surgeon and the complexity of the case.…”
Section: Discussionmentioning
confidence: 99%
“…Chakraborthy et al, and Shantini et al reported a wound infection rate of 5% and 5.7% respectively in TAH group which was similar to our study finding. 12,25 The reason behind higher rates of infection can be, as TAH is a more extensive operation, wound infection chances are more if proper wound care was not taken.…”
Section: Discussionmentioning
confidence: 99%
“…28 Chakraborty S et al reported one case of bladder injury in NDVH group. 25 Chavhan RP et al, stated that there is one case of bowel injury in TAH group. 23 Mehta K et al, reported one case of bladder injury in NDVH group and one case of bowel injury in TAH group and 4 cases of ureteric injury in TAH group.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 2 ] Even though abdominal hysterectomy is more invasive, it is still the most common route for hysterectomy, especially in rural areas, because firstly the patients are unaware of the benefits of laparoscopic hysterectomies, secondly the cost of surgery through abdominal route is less, and thirdly most of the surgeons find it easy and convenient to perform. [ 3 ] Minimally invasive surgeries such as nondescent vaginal hysterectomy (NDVH), laparoscopy-assisted vaginal hysterectomy (LAVH), and total laparoscopic hysterectomy (TLH) offer cosmetic benefit, and recovery is faster over the routine abdominal hysterectomy but requires more technical skills. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] Minimally invasive surgeries such as nondescent vaginal hysterectomy (NDVH), laparoscopy-assisted vaginal hysterectomy (LAVH), and total laparoscopic hysterectomy (TLH) offer cosmetic benefit, and recovery is faster over the routine abdominal hysterectomy but requires more technical skills. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%